#TITLE_ALTERNATIVE# - Nabila Chinta (NIM: 10213079), Ludya
In macroeconomic, financial condition of a country can be seen by an indicator called Gross Domestic Product or GDP, that defined as the value of all goods and services produced in a given country in a given period of time[1]. In other side, there is a concept of stock. Financial condition of a company can be seen by its stock price dynamic. This report will contain the result of a research which observe the economic condition of Indonesia by arrange some networks from stock close prices. The method used to construct the network is the Kruskal algorithm which will produce MST type network. In physics, the method can be applied in studies related to the lattice of a crystal. The results of this research shows that the network of stock sectors per year is in line with the Indonesian GDP growth rate of 2014-2016. This alignment proves that the network of stock sectors can be used for the analysis of economic conditions. It is also known that the most influential share sector, in the same period, is the Industry sector while the most influential stock is BSDE.